STRUKTUR TATA KELOLA EKONOMI LOKAL DALAM SEKTOR KERAJINAN GERABAH : “Local Economic Governance Structure in Pottery Industry: A Case Study of Global Value Chain Analysis in West Nusa Tenggara” - iskandar safitri; safitri purnami (UIN Mataram, 2022)
The declining export value of pottery in West Nusa Tenggara Province became a trend since 2006-2007. There are atleast two basic reasons of this significant decreasing, first the lessening numbers of export caused by global economic crisis, second the lack of competitiveness of the sector. The article questions about the structure of governance of the industry. Focusing on the issue will bring explanation what caused the industry has a quite low competitiveness in global market. The research itself is a qualitative research with global value chain approach. The study shows that there are two types of governance structure in the industry. The buyer-driven type of governance is built between local producer and global buyer in international trade context, while a more equal structure established in local market between local producer dan local buyer, or called as producer-driven with arms-length character. Meanwhile, the lack of competitiveness is also caused by the upgrading capacity, which tends to be a more static upgrading. The lack of upgrading capacity happened due to rents drain, where the rents that once existed in the community are getting dim due to the role of the government in building synergy and rents is considered small.